Art/Design Education Resiliency: "Staying with the Trouble" - Patterson, Pam (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2024)
Art/Design Education Resiliency: “Staying with the Trouble” references Donna Haraway’s call to commit to, and persevere in, realising connections as kin in a distressed world. Pam Patterson reviews a community research project, COVID-Anxiety, looking at the promise of laterally structured and collegially organized art educational communities of practice. Independent self-facilitated research communities such as these composed of students, staff, and faculty can inform research and build capacity for practice in art education. Comparing this success to the failed establishment of a Disability Caucus that followed, she pursues an explicatory reflective writing that locates her study in time, place, and situation. She further uses these reflections to develop a metatext that identifies a theory around dialogic/dialect process use for the establishment – and potential success – of co-learning art and design educational communities of practice (CoPs).